Shape Memory Soft Robotics with Yield Stress Fluids - Jackson Kyle Wilt; Johannes T. B. Overvelde; Corentin Coulais (Advanced Intelligent Systems, 2023)
Biological movement is a source of inspiration for designing soft robots that use fluidic actuation for adaptive gripping and locomotion. While many biological systems use networks of non‐Newtonian fluid for movement, to date, most soft robots use Newtonian fluids or pneumatics. Herein, yield stress fluids to manufacture and operate soft devices are exploited, particularly to create soft actuators that exhibit shape memory. Our soft robots are fabricated through embedded 3D printing where the suspension media is a yield stress fluid. Moreover, this complex fluid is encapsulated and used as the hydraulic transmission fluid. Diagnostic designs are developed to characterize the force and shape memory of the yield stress fluid, and the findings are used to create a gripper common in modern soft robotic applications. The diagnostic devices have deformable reservoirs that demonstrate force response, flow behavior, and deformation profiles dependent on the yield stress features of the transmission fluid. The actuation using the yield stress fluid from the retained suspension media creates avenues for partial shape retention and unconventional expansion from localized fluid flow. Looking toward the future of soft robotics, these fabrication and operational approaches using yield stress fluids can provide greater tunability for applications requiring nonlinear actuation and shape memory.